Efektifitas Modul Peltier TEC-12706 Sebagai Generator Dengan Memanfaatkan Eenergi Panas Dari Modul Peltier TEC-12706 - Fikri, Hafidh Abdurrohman Al; , Ir. Abdul Basith, MT (2016)
Peltier module is one component of which is often used as a thermoelectric cooler on the CPU box, a mini fridge in cars and various cooling devices on a small scale. Pertier module works on the principle of peltier where he will lead the process of heat absorption and heat release on each side of the peltier chip. Conditions such as these result in a temperature difference can be very significant at the sides of the peltier chip. This study examined the effectiveness of a Peltier module to be operated sabagai generator using the Seebeck effect principle owned by peltier modules, where the generator takes advantage of the heat energy generated by a Peltier module to another. Utilization of these two principles, namely the Seebeck effect and Peltier effect in which 6 pieces peltier modules arranged so as to form a cube with each side consisting of pieces peltier modules and use some comparisons in its utilization as a generator and as a producer of heat. Test of which has been done is a ratio of 2: 4, 4: 2 and 3: 3 (heat-: generator). The results showed that of the three combinations have shown the ineffectiveness of TEC-12706 peltier modules as a generator used peltier with another of the same type as heat producer